Vaccination of cattle with the N terminus of LppQ of Mycoplasma mycoides subsp. mycoides results in type III immune complex disease upon experimental infection - Mulongo, Musa M.; Frey, J.; Smith, K.; Schnier, C.; Wesonga, H.O.; Naessens, Jan; McKeever, Declan J. (American Society for Microbiology, 2015)
Contagious bovine pleuropneumonia (CBPP) is a serious respiratory disease of cattle caused by Mycoplasma mycoides subsp. mycoides. Current vaccines against CBPP induce short-lived immunity and can cause severe postvaccine reactions. Previous studies have identified the N terminus of the transmembrane lipoprotein Q (LppQ-N′) of M. mycoides subsp. mycoides as the major antigen and a possible virulence factor. We therefore immunized cattle with purified recombinant LppQ-N′ formulated in Freund's adjuvant and challenged them with M. mycoides subsp.mycoides. Vaccinated animals showed a strong seroconversion to LppQ, but they exhibited significantly enhanced postchallenge glomerulonephritis compared to the placebo group (P = 0.021). Glomerulonephritis was characterized by features that suggested the development of antigen-antibody immune complexes. Clinical signs and gross pathological scores did not significantly differ between vaccinated and placebo groups. These findings reveal for the first time the pathogenesis of enhanced disease as a result of antibodies against LppQ during challenge and also argue against inclusion of LppQ-N′ in a future subunit vaccine for CBPP.